Tuition Fees and Educational Attainment - Jan Bietenbeck; Jan Marcus; Felix Weinhardt (Institute of Labor Economics (IZA), 2020)
Following a landmark ruling by the Constitutional Court in 2005, more than half of Germany's universities started charging tuition fees, which also applied to incumbent students. We exploit this unusual lack of grandfathering together with register data covering the universe of students to show that tuition fees increased degree completion among incumbent students. Investigating mechanisms, we do not find that educational quality changed but that incumbent students raised their study effort. In line with previous international evidence, we also find that tuition fees decreased university enrollment among high school graduates. Combining our results, we show that tuition fees did not change overall educational attainment much because the positive effect on degree completion offset the negative effect on enrollment. We conclude by discussing policies to increase overall attainment, which take into account the opposing effects of fees around the zero-price margin.
Keywords: I23; I22; I28; 330; tuition fees; higher education